Answer:
![v_B/v_A=√(3)](https://img.qammunity.org/2021/formulas/physics/college/owuw8p7xyxdfn7x6uuqy1zqnhl53uk3t55.png)
Step-by-step explanation:
Consider the two kinematic equations for velocity and position of an object falling due to the action of gravity:
![v=-g\,t\\ \\position=-(1)/(2) g\,t^2](https://img.qammunity.org/2021/formulas/physics/college/13wr8sqwhd4kgqn8rkt87ozq5xa1int17m.png)
Therefore, if we consider
the time for the object to reach point A, and
the time for it to reach point B, then:
![v_A=-g\,t_A\\v_B=-g\,t_B\\(v_B)/(v_A)= (-g\,t_B)/(-g\,t_A) =(t_B)/(t_A)](https://img.qammunity.org/2021/formulas/physics/college/ei8nr6ghtn2lv8o5ch7ot7weuh6coic6jz.png)
Let's work in a similar way with the two different positions at those different times, and for which we have some information;
![x_A=-x=-(1)/(2)\, g\,t_A^2\\x_B=-3\,x=-(1)/(2)\, g\,t_B^2\\ \\(x_B)/(x_A) =(t_B^2)/(t_A^2) \\(t_B^2)/(t_A^2)=(-3\,x)/(-x) \\(t_B^2)/(t_A^2)=3\\((t_B)/(t_A))^2=3](https://img.qammunity.org/2021/formulas/physics/college/3f2hu73agn9dv5idtmv9ajx87is8301lf0.png)
Notice that this quotient is exactly the square of the quotient of velocities we are looking for, therefore:
![((t_B)/(t_A))^2=3\\((v_B)/(v_A))^2=3\\ (v_B)/(v_A)=√(3)](https://img.qammunity.org/2021/formulas/physics/college/1emabpb7lg9dktgh2cv8c4yyo7ct8k2ky5.png)